Analysis of Fingerprint Patterns in the people of the Laut Dendang sub-district, Percut Sei Tuan, Deli Serdang - azira rahman purba; Ummi Nur Afinni Dwi Jayanti; Wanda Syafitri; Sari Putri Ramadhani Tambunan; Azra Khairunnisa; Zahwa Adiesty; Destri Br Maha (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2023)
Fingerprints are important anthropological data because they are the key to the heredity code and also play a role important in determining a person's identity, biological origin, and race. Fingerprint patterns are formed as the fetus ages 13 weeks – 24 weeks. The tools used are stampe pads, lup (magnifying glass), and wet wipes. While the material is the fingers of the residents. This research is descriptive research, in which the researcher makes observations using direct survey methods to the field or so-called by going out into the field. Retrieval of fingerprint patterns by pressing one finger at a time on the padm stamp and stamped on the observation sheet that has been provided by the researcher. The results of probandus were observed in as many as 100 probandus in Lau Dendang District with 34 males sex and 66 females sex. The dominant number of tendrils is the "Plain Loop" which is owned by almost all of the community. And most of the probands are among the mothers who have the most Plain Loops and relatively the same number of tendrils. There are 11 probands that have 10 fingers in the form of "Plain Loop" or just the type. But the number of tendrils that are different characterizes why fingerprints can vary. While the "Arch" fingerprint model is the least owned by the public because the pattern is less common and recessive.